‘White People All Over’: Refugee Performance, Fictional Aesthetics, and Dramaturgies of Alterity-Empathy - Corrêa, Graça P. (2020)
This article by Graça P. Corrêa and Szabolcs Musca follows the production process of Passajar, an immersive participatory theatre project collaboratively created by four theatre-makers and refugees from Congo, Iran, Iraq, Syria and Zimbabwe. Developed under the curatorship of Portuguese choreographer Madalena Victorino for Festival Todos in Lisbon, this multilingual experimental work focused on representing migrant experiences through a postdramatic artistic gaze. The production refused the forms of testimonial theatre and with it the contradictory role of facilitators, opting instead for a multidimensional fictional aesthetics practice. In this article the authors explore how Passajar performance and dramaturgical processes address difference in actual creative practice; and what are the ‘refugeedom’ aesthetics and ethical affects being generated by working with refugee participants. Similar to a growing number of non-verbatim migrant theatre initiatives, Passajar switched from the real to the fictitious via non-realistic representations and processes of abstraction. Arguably, this practice went against victimhood narratives, but does suspending traditional means of identification and empathy help develop new understandings on migration, or, on the contrary create detachment in audiences? What are the ethical consequences to audiences and refugee participants alike? Drawing upon philosophical concepts by Henri Bergson, Baruch Spinoza and Gilles Deleuze, the article examines how they critically contribute towards a discussion of the dramaturgies of alterity and empathy that were deployed in Passajar. By reflecting on both rehearsal process and final production, it reveals the ethical affects of Passajar, as well as transformative alternatives for migrant representation beyond the stage.